Pelatihan dan Pendampingan Penggunaan Media Pembelajaran Daring untuk Orang Tua di Kelurahan Kratonan Kota Surakarta - Muin Abdullah; Nunung Alfiah; Abdullah Hasan At Taufiq (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
During the COVID-19 pandemic, people are facing many problems. One of the problems faced is online learning, which the government is now promoting. The main problems in online learning start with teachers who only give assignments without clear explanations to their students, students who do not have technological devices such as smartphones, and no internet network. Moreover, students' learning motivation needs to be improved in dealing with online learning's lack of understanding of parents on how to use online media so that they cannot provide maximum assistance to children at home. This online learning training and mentoring program focused on increasing the capacity of parents to assist children's learning. The methodology used is the lecture, discussion, question and answer, and practical simulation. The results achieved are by increasing the ability of parents to use online media in learning.